Sinonasal extranodal NK/T-cell lymphoma presenting with torrential epistaxis / Siti Nor Ashiah Johari ... [et al.] - Johari, Siti Nor Ashiah; Mohamad, Sakinah; Nadarajan, Chandran; Abdullah, Abu Dzarr; Mat Lazim, Norhafiza; Mohamad, Irfan (Faculty of Medicine, 2021)
Extranodal sinonasal natural killer/T-cell lymphoma is known for its locally destructive nature at the midface region. The initial presentations are related to the localized granulomatous-like lesion usually in the nasal cavity that may lead to symptoms of nasal obstruction, discharge, hyposmia and epistaxis. Advanced disease may present with a rapid dissemination of disease to the liver, spleen, skin, lymph nodes, and bone marrow hence poorer prognosis. We report a case of a young lady with rapid progression of extranodal sinonasal NK/T cell lymphoma with torrential tumour bleeding from the oral and nasal cavities compromising the upper airway patency, which warranted an emergency tracheostomy and arterial embolization.